“The Yak”—A remarkable animal living in a harsh environment: An overview of its feeding, growth, production performance, and contribution to food security - Ali Mujtaba Shah; Ali Mujtaba Shah; Iqra Bano; Izhar Hyder Qazi; Maharach Matra; Metha Wanapat (Frontiers in Veterinary Science, 2023)
Yaks play an important role in the livelihood of the people of the Qinghai-Tibet Plateau (QTP) and contribute significantly to the economy of the different countries in the region. Yaks are commonly raised at high altitudes of ~ 3,000–5,400 m above sea level. They provide many important products, namely, milk, meat, fur, and manure, as well as social status, etc. Yaks were domesticated from wild yaks and are present in the remote mountains of the QTP region. In the summer season, when a higher quantity of pasture is available in the mountain region, yaks use their long tongues to graze the pasture and spend ~ 30–80% of their daytime grazing. The remaining time is spent walking, resting, and doing other activities. In the winter season, due to heavy snowfall in the mountains, pasture is scarce, and yaks face feeding issues due to pasture scarcity. Hence, the normal body weight of yaks is affected and growth retardation occurs, which consequently affects their production performance. In this review article, we have discussed the domestication of yaks, the feeding pattern of yaks, the difference between the normal and growth-retarded yaks, and also their microbial community and their influences. In addition, blood biochemistry, the compositions of the yaks' milk and meat, and reproduction are reported herein. Evidence suggested that yaks play an important role in the daily life of the people living on the QTP, who consume milk, meat, fur, use manure for fuel and land fertilizer purposes, and use the animals for transportation. Yaks' close association with the people's well-being and livelihood has been significant.